Efficient and long-service-life electrode for alkaline electrolyzed water and preparation method of efficient and long-service-life electrode

Through vacuum multi-arc ion plating, the alloy catalytic layer was deposited on the nickel substrate, and combined with alkaline erosion and pore formation, the problems of complex electrode preparation technology and short life are solved, and high-efficiency, long-life alkaline electrolytic electrodes are achieved. Preparation reduces cost and energy consumption.

CN119144992APending Publication Date: 2024-12-17SUZHOU XIBEIYOU HYDROGEN ENERGY TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411470207.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The electrode preparation process and poor reproducibility in existing alkaline electrolytic hydrogen production equipment have complex electrode preparation processes, resulting in high energy consumption, high cost and short electrode life, limiting the commercial application of the technology.

Method used

The catalytic layer is deposited by vacuum multi-arc ion plating using nickel substrate and alloy target. The alloy target is composed of metals such as Ni, Fe, Mo, Co, Ga, Cd, Al, Zn, Sn, etc., and is pretreated and vacuumed. Arc ion plating method prepares a catalytic layer with high specific surface area, and combines alkali erosion to create pores to form high-efficiency and long-life electrodes.

Benefits of technology

The high activity and strong binding force of the non-precious metal catalytic layer are achieved, which significantly improves the service life of the electrode and material cost-effectiveness, and reduces energy consumption and raw material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144992A_ABST
    Figure CN119144992A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient long-life alkaline electrolyzed water electrode which comprises a nickel base material and a catalytic layer, and the catalytic layer is deposited on the surface of the nickel base material through an alloy target material by a vacuum multi-arc ion plating method. The alloy target material is composed of Ni, a metal element X having strong binding energy with hydrogen, a metal element Y having weak binding energy with H and a metal element Z used for pore forming. The invention further discloses a preparation method which comprises the following steps: preparing an alloy target material, depositing an alloy plating layer on a nickel base material by utilizing vacuum multi-arc ion plating, and then placing the nickel base material in alkali liquor for pore forming to obtain the electrode. By using the non-noble metal, the preparation cost is effectively reduced, good activity of the non-noble metal catalyst layer is ensured, the coating is not easy to fall off, and the service life is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogen production by alkaline water electrolysis, and in particular to an electrode for alkaline water electrolysis with high efficiency and long service life and a preparation method thereof. Background Art

[0002] As an energy carrier, hydrogen can not only meet global energy needs under the current "dual carbon" goal, but also reduce CO2 emissions, and play an important role in the future development of the energy industry. Among them, alkaline water electrolysis technology equipment has low manufacturing costs, long equipment service life, and low equipment operation and maintenance costs. It is the most commercialized hydrogen production technology. In practical applications, the performance and life of the electrode are key factors affecting the energy consumption and life of alkaline water electrolysis hydrogen production equipment. Therefore, the development of a high catalytic activity and long life hydrogen evolution electrode is an important part of promoting the progress of the alkaline water electrolysis hydrogen production technology industry.

[0003] Precious metals such as Pt, Ir, and Ru are ideal HER catalysts, but their scarcity and high cost limit their widespread application. Therefore, it is of great significance to design a cost-effective, active and efficient non-precious metal catalytic coating electrode.

[0004] At present, the main electrode preparation methods in alkaline water electrolysis technology include plasma thermal spraying, electrodeposition, magnetron sputtering, etc. Among them, the electrodeposition method is used to prepare alloy coatings, which is complex and difficult to control, and has poor reproducibility. Although the plasma spraying process has good coating reproducibility and is one of the methods with the highest commercial layer degree, the high temperature and low utilization rate of the spraying material during the spraying process lead to high energy consumption and raw material costs. In addition, the insufficient coating adhesion strength leads to coating shedding, and the short electrode life is still a bottleneck problem in the real commercial application of alkaline electrolytic cells. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an efficient and long-life alkaline water electrolysis electrode and a preparation method thereof. The use of non-precious metals effectively reduces the preparation cost and ensures that the non-precious metal catalytic layer has good activity, the coating is not easy to fall off, and the service life is greatly improved.

[0006] In order to solve the above technical problems, the present invention provides a high-efficiency and long-life alkaline water electrolysis electrode, comprising a nickel substrate and a catalytic layer, wherein the catalytic layer is deposited on the surface of the nickel substrate by a vacuum multi-arc ion plating method using an alloy target, wherein the alloy target is composed of Ni, a metal element X having a strong binding energy with hydrogen, a metal element Y having a weak binding energy with H, and a metal element Z for pore formation.

[0007] Furthermore, the metal element X having strong binding energy with hydrogen is selected from one of Fe, Mo, and Co, the metal element Y having weak binding energy with H is selected from one of Ga, Cd, and In, and the metal element Z used for pore formation is selected from one of Al, Zn, and Sn.

[0008] Furthermore, the metal powders in the alloy target are prepared into the alloy target by a smelting method according to an atomic ratio of Ni:X:Y:Z=50-60:5-10:5-10:30.

[0009] Furthermore, the thickness of the catalytic layer is 3-10 μm.

[0010] Furthermore, the nickel substrate is a nickel woven mesh, a stretched nickel mesh, a nickel foam or a nickel felt.

[0011] A method for preparing an electrode for high-efficiency and long-life alkaline water electrolysis comprises the following steps:

[0012] A. First, prepare the alloy target and pre-treat the nickel substrate, and perform sandblasting, degreasing, cleaning and drying in sequence; the purpose of pre-treatment is to roughen the surface of the substrate, on the one hand, increase the bonding area between the coating and the substrate to achieve the purpose of enhancing the bonding force of the coating, and on the other hand, increase the specific surface area of ​​the coating;

[0013] B. Place the pre-treated nickel substrate on the rotating rack in the vacuum chamber, turn on the rotating rack, and perform vacuuming, argon gas introduction, and ion source cleaning in sequence; during ion source cleaning, positively charged argon ions are accelerated and move toward the workpiece under the action of the electric field, violently bombarding the surface of the workpiece. This process sputters out the pollutants and surface oxide layer on the surface of the workpiece, enhances the activity of the workpiece surface, is conducive to enhancing the bonding force between the coating and the substrate, and increases the life of the electrode;

[0014] C. After the ion source is cleaned, the temperature of the vacuum chamber is increased, the Ar given rate is adjusted, the vacuum degree of the vacuum chamber is stabilized, the bias voltage and the target current are turned on in sequence, and the alloy catalyst layer is deposited on the nickel substrate;

[0015] D. After the deposition is completed, maintain the vacuum degree and cool down naturally;

[0016] E. After the deposition is completed, a semi-finished product is obtained, and the semi-finished product is placed in an alkaline solution for corrosion and pore formation to form a catalytic layer with a high specific surface area to obtain a finished product.

[0017] Furthermore, the distance between the nickel substrate and the alloy target is 30-60 cm, the rotating speed is 0-100 rpm, and the vacuum degree reaches 2*10 -2After pa, argon gas is introduced at a given rate of 10-30 ml / min, the vacuum degree is maintained at 0.1-0.3 Pa, the bias voltage is 150-300 V, the ion source current is 2-4 A, and the surface bombardment time of the nickel substrate is 10-30 min.

[0018] Further, the temperature of the vacuum chamber is raised to 150-200° C., the given speed of argon gas is adjusted to maintain the vacuum degree in the vacuum chamber at 0.5 Pa, the bias voltage is 150-300 V, the target current is 60-140 A, and the deposition is continued for 1-6 hours.

[0019] Furthermore, the natural cooling time is at least 3 hours.

[0020] Furthermore, the alkali solution is a 10-30wt% sodium hydroxide or potassium hydroxide solution, the alkali solution temperature is 40-80°C, and the corrosion time is 10-20h.

[0021] Beneficial effects of the present invention:

[0022] The present invention combines a metal element with a strong H adsorption effect with a metal with a weak H adsorption effect to form an alloy, reaches a balance point for the adsorption and desorption of H, and prepares a non-precious metal alloy electrode. The electrode has high catalytic activity and low material cost.

[0023] The electrode catalyst layer is prepared by vacuum multi-arc ion plating. The coating has a strong bonding force with the substrate, which greatly increases the service life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the microscopic morphology of the electrode prepared by the present invention;

[0025] Figure 2 are the overpotential curves of the comparative examples and embodiments of the present invention at different current densities;

[0026] Figure 3 It is the tE aging curve of each comparative example and embodiment in the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0028] The high-efficiency and long-life alkaline water electrolysis electrode mentioned in the present invention comprises a nickel substrate and a catalyst layer, wherein the catalyst layer is deposited on the surface of the nickel substrate by a vacuum multi-arc ion plating method using an alloy target material, wherein the alloy target material is composed of N i. It is composed of a metal element X with strong binding energy to hydrogen, a metal element Y with weak binding energy to H, and a metal element Z used for pore formation. During the use of the electrode, if the bonding between the catalytic active site of the element and H is weak, it is not conducive to the adsorption and conversion of H. If the bonding between the catalytic active site of the element and H is too strong, it is not conducive to the desorption of H. Only when the bonding between the catalytic active site and H is moderate can the optimal HER catalytic activity be exhibited. By flexibly regulating the synergistic effect between the metal components in the alloy, the catalyst has a moderate adsorption capacity, which is neither too strong nor too weak, so that the reactants can be effectively adsorbed on the catalyst surface and can be easily desorbed from the catalyst surface. Based on the idea of ​​achieving a balance between strong and weak coordination, the metal with strong H binding energy and the metal with weak H binding energy are combined to achieve the optimal combination of H binding energy, thereby achieving the purpose of optimizing catalytic activity, so that the interaction between the catalyst and the reactant reaches a "just right" level, thereby ensuring the efficient conduct of the catalytic reaction; the microscopic morphology of the prepared electrode is as follows Figure 1 shown.

[0029] Specifically, the metal element X having strong binding energy with hydrogen is selected from one of Fe, Mo, and Co, the metal element Y having weak binding energy with H is selected from one of Ga, Cd, and In, and the metal element Z used for pore formation is selected from one of Al, Zn, and Sn. Fe, Mo, and Co show too strong adsorption to H, that is, they have higher H binding energy. Al, Zn, and Sn show too weak adsorption to H, that is, they have lower H binding energy.

[0030] In the use of the above-mentioned metal elements, the optimal combination is the key to the preparation. The metal powders in the alloy target are in an atomic ratio of Ni:X:Y:Z=50-60:5-10:5-10:30. Based on this, the following comparative examples and embodiments are combined to provide a detailed description:

[0031] Comparative Example 1

[0032] Comparative Example 1 is an electrode in which the substrate without coating is roughened and degreased, and the detailed steps are as follows:

[0033] The substrate is sandblasted and cleaned in sequence, and then the sandblasted substrate is immersed in a degreasing liquid, and the dirt and grease on the surface of the substrate are removed by ultrasonic wave, and then the substrate is washed with clean water and dried for later use;

[0034] Comparative Example 2

[0035] Comparative Example 2 is a commercial Raney nickel electrode currently available on the market after activation, which is directly tested and compared; Example 1

[0036] In this embodiment, Ni 60 Co5Ga5Al 30 Alloy target material, catalytic coating deposition using vacuum multi-arc ion plating process.

[0037] Electrode substrate pretreatment: sandblast and clean the substrate in sequence, then soak the sandblasted substrate in degreasing liquid, ultrasonically remove dirt and grease on the surface of the substrate, wash with clean water and dry for later use;

[0038] The pre-prepared Ni 60 Co5Ga5Al 30 The alloy target is installed on the target station and is ready for use;

[0039] The pretreated nickel substrate sample is placed on the rotating rack in the vacuum chamber, with the distance between the target and the workpiece being 30 cm. The rotating rack is turned on and the rotating rack speed is 40 rpm.

[0040] Start the vacuum pump and evacuate the vacuum chamber to a vacuum degree of 2*10 -2 At pa, the argon valve was opened, the argon gas rate was set at 20 ml / min, the vacuum degree was maintained at 0.3 pa, the workpiece bias voltage was turned on at 150 V, the ion source current was turned on at 4 A, the nickel substrate was bombarded on the surface for 20 min, and the ion source cleaning was completed;

[0041] Turn on the heating device to heat the vacuum chamber and maintain the temperature at 150-200°C;

[0042] Adjust the given speed of argon gas to maintain the vacuum degree in the vacuum chamber at 0.5Pa, maintain the workpiece bias voltage at 150V, turn on the target current, the target current is 80A, the target material starts sputtering, and the deposition continues for 3h;

[0043] After the sputtering is completed, the target current is turned off, the bias voltage is turned off, the air inlet valve is closed, and the vacuum is maintained for natural cooling for 4 hours;

[0044] The electrode sample was taken out, and the electrode coating was subjected to alkali etching to form pores, wherein the alkali solution was a 20wt% sodium hydroxide solution, the alkali solution temperature was 50°C, and the etching time was 20h, so as to form a catalytic layer with a high specific surface area;

[0045] Example 2

[0046] In this embodiment, Ni 60 Mo5Cd5Zn 30 Alloy target material, catalytic coating deposition using vacuum multi-arc ion plating process.

[0047] Electrode substrate pretreatment: sandblast and clean the substrate in sequence, then soak the sandblasted substrate in degreasing liquid, ultrasonically remove dirt and grease on the surface of the substrate, wash with clean water and dry for later use;

[0048] The pre-prepared Ni 60 Mo5Cd5Zn 30 The alloy target is installed on the target station and is ready for use;

[0049] The pretreated nickel substrate sample is placed on the rotating rack in the vacuum chamber, with the distance between the target and the workpiece being 40 cm. The rotating rack is turned on and the rotating rack speed is 60 rpm.

[0050] Start the vacuum pump and evacuate the vacuum chamber to a vacuum degree of 3*10 -2 At pa, the argon valve was opened, the argon gas was given at a rate of 20 ml / min, the vacuum degree was maintained at 0.4 pa, the workpiece bias voltage was turned on to 150 V, the ion source current was turned on to 4 A, the nickel substrate was bombarded on the surface for 30 minutes, and the ion source cleaning was completed;

[0051] Turn on the heating device to heat the vacuum chamber and maintain the temperature at 150-200°C;

[0052] Adjust the given speed of argon gas to maintain the vacuum degree in the vacuum chamber at 0.5Pa, maintain the workpiece bias voltage at 200V, turn on the target current, the target current is 100A, the target material starts sputtering, and the deposition continues for 4h;

[0053] After the sputtering is completed, the target current is turned off, the bias voltage is turned off, the air inlet valve is closed, and the vacuum is maintained for natural cooling for 4 hours;

[0054] The electrode sample was taken out, and the electrode coating was subjected to alkali etching to form pores, wherein the alkali solution was a 20wt% sodium hydroxide solution, the alkali solution temperature was 50°C, and the etching time was 20h, so as to form a catalytic layer with a high specific surface area;

[0055] Example 3

[0056] This embodiment uses Ni 50 Fe 10 I n 10 Sn 30 Alloy target material, catalytic coating deposition using vacuum multi-arc ion plating process.

[0057] Electrode substrate pretreatment: sandblast and clean the substrate in sequence, then soak the sandblasted substrate in degreasing liquid, ultrasonically remove dirt and grease on the surface of the substrate, wash with clean water and dry for later use;

[0058] The pre-prepared Ni 50 Fe 10 I n 10 Sn 30 The alloy target is installed on the target station and is ready for use;

[0059] The pretreated nickel substrate sample is placed on the rotating rack in the vacuum chamber, with the distance between the target and the workpiece being 50 cm. The rotating rack is turned on and the rotating rack speed is 60 rpm.

[0060] Start the vacuum pump and evacuate the vacuum chamber to a vacuum degree of 2*10 -2 At pa, the argon valve was opened, the argon gas was given at a rate of 25 ml / min, the vacuum degree was maintained at 0.5 pa, the workpiece bias voltage was turned on to 150 V, the ion source current was turned on to 4 A, the nickel substrate was bombarded on the surface for 30 minutes, and the ion source cleaning was completed;

[0061] Turn on the heating device to heat the vacuum chamber and maintain the temperature at 150-200°C;

[0062] Adjust the given speed of argon gas to maintain the vacuum degree in the vacuum chamber at 0.4Pa, maintain the workpiece bias voltage at 200V, turn on the target current, the target current is 100A, the target material starts sputtering, and the deposition continues for 5h;

[0063] After sputtering, turn off the target current, turn off the bias voltage, close the air inlet valve, maintain the vacuum and cool down naturally for 5 hours;

[0064] The electrode sample was taken out, and the electrode coating was subjected to alkali etching to form pores. The alkali solution was a 25wt% sodium hydroxide solution, the alkali solution temperature was 40°C, and the etching time was 15h to form a catalytic layer with a high specific surface area;

[0065] Example 4

[0066] This embodiment uses Ni 50 Mo 10 I n 10 Al 30 Alloy target material, catalytic coating deposition using vacuum multi-arc ion plating process.

[0067] Electrode substrate pretreatment: sandblast and clean the substrate in sequence, then soak the sandblasted substrate in degreasing liquid, ultrasonically remove dirt and grease on the surface of the substrate, wash with clean water and dry for later use;

[0068] The pre-prepared Ni 50 Mo 10 I n 10 Al 30 The alloy target is installed on the target station and is ready for use;

[0069] The pretreated nickel substrate sample is placed on the rotating rack in the vacuum chamber, with the distance between the target and the workpiece being 50 cm. The rotating rack is turned on and the rotating rack speed is 50 rpm.

[0070] Start the vacuum pump and evacuate the vacuum chamber to a vacuum degree of 2*10 -2At pa, the argon valve was opened, the argon gas rate was set to 30 ml / min, the vacuum degree was maintained at 0.4 pa, the workpiece bias voltage was turned on to 250 V, the ion source current was turned on to 4 A, the nickel substrate was bombarded on the surface for 20 min, and the ion source cleaning was completed;

[0071] Turn on the heating device to heat the vacuum chamber and maintain the temperature at 150-200°C;

[0072] Adjust the given speed of argon gas to maintain the vacuum degree in the vacuum chamber at 0.4Pa, maintain the workpiece bias voltage at 200V, turn on the target current, the target current is 120A, the target material starts sputtering, and the deposition continues for 6h;

[0073] After the sputtering is completed, the target current is turned off, the bias voltage is turned off, the air inlet valve is closed, and the vacuum is maintained for natural cooling for 4 hours;

[0074] The electrode sample was taken out, and the electrode coating was subjected to alkali etching to form pores. The alkali solution was a 25wt% sodium hydroxide solution, the alkali solution temperature was 50°C, and the etching time was 12h to form a catalytic layer with a high specific surface area;

[0075] The above two comparative examples and four embodiments were subjected to hydrogen evolution overpotential test under high current density, coating adhesion test and electrolytic cell long-term life test. The specific experimental parameters and performance comparison parameters are as follows:

[0076] Table 1 is the atomic ratio of each element in the embodiment, as shown in the following table:

[0077]

[0078] Table 2 shows the overpotentials of the electrodes of the embodiments and comparative examples at different current densities:

[0079]

[0080] Table 3 shows the voltage attenuation and performance attenuation percentage:

[0081]

[0082] As shown in Table 1, the ratio of the number of atoms of each element in the catalyst layer prepared by Examples 1-4 obtained by EDS scanning, it can be seen from the table that the actual atomic ratio is slightly different from the atomic ratio in the target material, and the reasons for this difference are as follows: First, the substrate is nickel, and more Ni signals will be received during EDS scanning, so the Ni content is higher than the nickel content in the target material; secondly, in the process of vacuum ion plating, when argon ions are accelerated by the electric field to bombard the target material, the atomic mass of each element in the target material is different, and the probability of being sputtered is also different, and the coating cannot be completely carried out according to the atomic ratio of the target material; again, EDS is a semi-quantitative test method, and the ratio of the number of atoms of each element cannot be completely and accurately tested. Therefore, in actual testing, the ratio of the number of atoms of each element in the catalyst layer is slightly different from the ratio of the number of atoms in the target material. And only after the atomic number ratio in the alloy target material is effectively determined, the atomic number ratio of each element in the catalyst layer can meet the requirements.

[0083] Figure 2 The curves were prepared using an Autolab electrochemical workstation, with mercury / mercuric oxide as the reference electrode, to simulate the actual working conditions of an alkaline electrolyzer. The current densities (1000-8000 A / m 2 ) of the lower electrode, the detailed data are shown in Table 2. The results show that the overpotential of the catalytic coating obtained by the vacuum multi-arc ion plating method and the multi-element alloy is significantly improved under the working conditions close to the actual operation, compared with the roughened nickel mesh and the Raney nickel electrode currently used in the market. 2 The overpotential of the nickel mesh is 194mV lower than that of the bare nickel mesh at a current density of 1000A / m 2 The overpotential of the bare nickel mesh is 148 mV lower at this current density.

[0084] Figure 3 The curve is a test of the comparative example and the example samples using a 5cm*5cm electrolytic cell test fixture, with an operating temperature of 85°C, 30wt% KOH, and an operating current density of 10000A / m 2 In the case of such high current density, the electrode life will decay rapidly. Table 3 shows the electrode life at 10000A / m 2 After running for 300 hours at the current density, the voltage attenuation and performance attenuation percentage are combined with Figure 3 It can be seen that after the Raney nickel has been running for a period of time, the cell voltage rises significantly, while the cell voltages of several samples of the present invention do not rise significantly, which is close to the rising trend of the light nickel mesh in comparative example 1. This test result is sufficient to show that the life of the present invention has been significantly improved.

[0085] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. An efficient and long-life alkaline water electrolysis electrode, characterized in that: The invention comprises a nickel substrate and a catalytic layer. The catalytic layer is deposited on the surface of the nickel substrate by a vacuum multi-arc ion plating method using an alloy target. The alloy target is composed of Ni, a metal element X having a strong binding energy with hydrogen, a metal element Y having a weak binding energy with H, and a metal element Z for forming holes.

2. The high-efficiency and long-life alkaline water electrolysis electrode according to claim 1, characterized in that: The metal element X having strong binding energy with hydrogen is selected from one of Fe, Mo and Co, the metal element Y having weak binding energy with H is selected from one of Ga, Cd and In, and the metal element Z used for pore formation is selected from one of Al, Zn and Sn.

3. The high-efficiency and long-life alkaline water electrolysis electrode according to claim 2, characterized in that: The metal powders in the alloy target material are prepared into the alloy target material by a smelting method according to the atomic number ratio of Ni:X:Y:Z=50-60:5-10:5-10:

30.

4. The high-efficiency and long-life alkaline water electrolysis electrode according to claim 1, characterized in that: The thickness of the catalytic layer is 3-10 μm.

5. The high-efficiency and long-life alkaline water electrolysis electrode according to claim 1, characterized in that: The nickel substrate is a nickel woven mesh, a stretched nickel mesh, a nickel foam or a nickel felt.

6. The method for preparing a high-efficiency and long-life alkaline water electrolysis electrode according to claim 3, characterized in that: The following steps are involved: A. First, prepare the alloy target and pre-treat the nickel substrate, and perform sandblasting, degreasing cleaning and drying in sequence; B. Place the pretreated nickel substrate on a rotating rack in a vacuum chamber, turn on the rotating rack, and perform vacuuming, argon gas introduction, and ion source cleaning in sequence; C. After the ion source is cleaned, the temperature of the vacuum chamber is increased, the Ar given rate is adjusted, the vacuum degree of the vacuum chamber is stabilized, the bias voltage and the target current are turned on in sequence, and the alloy catalyst layer is deposited on the nickel substrate; D. After the deposition is completed, maintain the vacuum degree and cool down naturally; E. After the deposition is completed, a semi-finished product is obtained, and the semi-finished product is placed in an alkaline solution for corrosion and pore formation to form a catalytic layer with a high specific surface area to obtain a finished product.

7. The method for preparing a high-efficiency and long-life alkaline water electrolysis electrode according to claim 6, characterized in that: The distance between the nickel substrate and the alloy target is 30-60 cm, the rotating speed is 0-100 rpm, and the vacuum degree reaches 2*10 - 2 After pa, argon gas is introduced at a given rate of 10-30 ml / min, the vacuum degree is maintained at 0.1-0.3 Pa, the bias voltage is 150-300 V, the ion source current is 2-4 A, and the surface bombardment time of the nickel substrate is 10-30 min.

8. The method for preparing a high-efficiency and long-life alkaline water electrolysis electrode according to claim 6, characterized in that: The temperature of the vacuum chamber is raised to 150-200°C, and the given speed of argon gas is adjusted to maintain the vacuum degree in the vacuum chamber at 0.5 Pa, the bias voltage is 150-300 V, the target current is 60-140 A, and the deposition is continued for 1-6 hours.

9. The method for preparing a high-efficiency and long-life alkaline water electrolysis electrode according to claim 6, characterized in that: The natural cooling time is at least 3 hours.

10. The method for preparing a high-efficiency and long-life alkaline water electrolysis electrode according to claim 6, characterized in that: The alkali solution is a 10-30wt% sodium hydroxide or potassium hydroxide solution, the alkali solution temperature is 40-80°C, and the corrosion time is 10-20h.

Citation Information

Cited By

  • Hydrogen evolution electrode for AEM electrolytic cell cathode and preparation method of hydrogen evolution electrode

    CN119372708A

  • A hydrogen evolution electrode for cathode of AEM electrolytic cell and preparation method thereof

    CN119372708B

  • Preparation method of nickel-molybdenum alloy water electrolysis hydrogen production electrode

    CN122382621A

  • Multi-layered water electrolysis electrode and manufacturing method therefor

    WO2026134883A1